Under the skin [videorecording (DVD)] - Glazer, Jonathan; Faber, Michael; Johansson, Scarlett, 1984- (Lionsgate, 2014)
An alien in the form of a voluptuous young woman combs the streets of Scotland in search of men. She lures a succession of lost souls into her otherworldly lair, where they are seduced, stripped of their humanity, and never heard from again.